How to be an Epicurean the ancient art of living well - Wilson, Catherine 1951- (Basic Books, 2019)
In How to Be an Epicurean, philosopher Catherine Wilson shows that Epicureanism isn't an excuse for having a good time: it's a means to live a good life. Although modern conveniences and scientific progress have significantly improved our quality of life, many of the problems faced by ancient Greeks -- love, money, family, politics -- remain with us in new forms. To overcome these obstacles, the Epicureans adopted a philosophy that promoted reason, respect for the natural world, and reverence for our fellow humans. By applying this ancient wisdom to a range of modern problems, from self-care routines and romantic entanglements to issues of public policy and social justice, Wilson shows us how we can all fill our lives with purpose and pleasure
Keywords: Epikureismus; Gutes Leben; Lebensführung; Epicureans (Greek philosophy); Philosophy, Ancient; Self-help publications